A New Active Cavitation Mapping Technique for Pulsed HIFU Applications – Bubble Doppler - Li, Tong (IEEE Trans Ultrason Ferroelectr Freq Control, 2014)
In this work, a new active cavitation mapping technique for pulsed high-intensity focused ultrasound (pHIFU) applications termed bubble Doppler is proposed and its feasibility tested in tissue-mimicking gel phantoms. pHIFU therapy uses short pulses, delivered at low pulse repetition frequency, to cause transient bubble activity that has been shown to enhance drug and gene delivery to tissues. The current gold standard for detecting and monitoring cavitation activity during pHIFU treatments is passive cavitation detection (PCD), which provides minimal information on the spatial distribution of the bubbles. B-mode imaging can detect hyperecho formation, but has very limited sensitivity, especially to small, transient microbubbles. The bubble Doppler method proposed here is based on a fusion of the adaptations of three Doppler techniques that had been previously developed for imaging of ultrasound contrast agents – color Doppler, pulse inversion Doppler, and decorrelation Doppler. Doppler ensemble pulses were interleaved with therapeutic pHIFU pulses using three different pulse sequences and standard Doppler processing was applied to the received echoes. The information yielded by each of the techniques on the distribution and characteristics of pHIFU-induced cavitation bubbles was evaluated separately, and found to be complementary. The unified approach - bubble Doppler – was then proposed to both spatially map the presence of transient bubbles and to estimate their sizes and the degree of nonlinearity.